PENGGUNAAN SISTIM INFORMASI GEOGRAFIS UNTUK PEMETAAN TINGKAT RAWAN BANJIR DI KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Abdur Rahman (EnviroScienteae, 2017)
This study aims to map the vulnerability of flood in Banjar district is based on variable rainfall, soil type, land cover, and slope. From the results of this study concluded that the level of vulnerability to flooding in South Kalimantan Banjar district can be categorized into five, namely; namely the vulnerability of flood-prone, flood potential is rather prone to flooding, flood-prone and highly prone to flooding. Areas of potential flooding are in part the District Aranio an area affected by potential flooding 12:15 Ha or 2.71%, District and Sub-district Martapura Aranio with an area of 85.36 hectares or 19.03% potential, River District Pinang, Mataraman, Astambul, Peat, partly Aranio and partly Pengaron. Areas affected by the floods is estimated an area of 18.72 ha, or the potential flooding of 4.17%. Sungai Pinang, Mataraman, Astambul, Peat, partly Aranio and partly Pengaron. Areas affected by the floods is estimated area of 227.65 hectares or 50.76% of the potential flooding. And districts Sungai Pinang, Mataraman, Astambul, Peat, partly Aranio and partly Pengaron. Areas affected by the floods is estimated area of 104.53 hectares or 23.31% of the potential flooding.